Language, ideology, and point of view - Simpson, Paul (Interface (London, England), 1993)
This systematic introduction to the concept of point of view in language explores the ways in which point of view is shaped by ideology. It focusses on the way in which people encode their beliefs and biases in a wide variety of media.